2020
DOI: 10.1186/s12870-020-02436-x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analyses provide insights into the homeostatic regulation of axillary buds in upland cotton (G. hirsutum L.)

Abstract: Background: The axillary bud is an important index of cotton plant-type traits, and the molecular mechanism of axillary bud development in upland cotton has not yet been reported. We obtained a mutant (designated mZ571) with a high-budding phenotype in axillary bud development from the low-budding phenotype variety G. hirsutum Z571 (CCRI 9A02), which provided ideal materials for the study of complex regulatory networks of axillary bud development. In this study, RNA sequencing was carried out to detect gene ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 62 publications
3
4
0
Order By: Relevance
“…In this work, the expression level of TPP7 was upregulated in the mtn1 mutant. This result was in agreement with previous studies on Arabidopsis [ 24 ], maize [ 25 ] and upland cotton [ 45 ], which indicated that a high expression level of TPPs could increase the tillering/branch number. The high expression level of the TPP7 gene was consistent with the high soluble sugar concentration and suggested that sugars are an energy source or nutrient aiding in bud growth in high-tillering centipedegrass.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this work, the expression level of TPP7 was upregulated in the mtn1 mutant. This result was in agreement with previous studies on Arabidopsis [ 24 ], maize [ 25 ] and upland cotton [ 45 ], which indicated that a high expression level of TPPs could increase the tillering/branch number. The high expression level of the TPP7 gene was consistent with the high soluble sugar concentration and suggested that sugars are an energy source or nutrient aiding in bud growth in high-tillering centipedegrass.…”
Section: Discussionsupporting
confidence: 93%
“…In addition to plant hormones, sugars are also necessary for tillering, as they can act as an early signal and provide energy during the tillering development process [ 44 , 45 , 46 ]. In this work, the soluble sugar content in the mtn1 mutant was higher than that of the wild-type.…”
Section: Discussionmentioning
confidence: 99%
“…Leaves of each lines were collected for library preparation and RNA-sequencing were performed using Illumina HiSeq 2000. DESeq2 program was used to identify differentially expressed genes, (log fold change ≥1 and FDR<0.05) were considered to be the cutoff threshold to determine differentially expressed genes [56][57][58][59]. All sequencing data have been deposited in SRA (www.ncbi.nlm.nih.gov/sra).The accession numbers are SRR12223945, SRR1652393, ERR5006257 and SRR1652403.…”
Section: Rna-sequencingmentioning
confidence: 99%
“…Programmed cell death (PCD) plays an important role during the development of pigment glands in Gossypium hirsutum leaf tissue [ 42 ]. Ethylene, which regulate the upstream signal molecular during PCD process, mediates the PCD signal by ROS [ 54 ]. Therefore, it is meaningful to investigate the expression pattern of GhERF105 gene in response to stress hormone ethylene stimuli.…”
Section: Resultsmentioning
confidence: 99%